Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan pada J&T Express Drop Center 08 Depok Jawa Barat - Siti Maryam; Pusporini Palupi Jamaludin; Paringsih Paringsih (JURNAL RISET MANAJEMEN (JURMA), 2024)
This study aims to determine the effect of Motivation and Work Discipline variables on Employee Performance at J&T Express Drop Center 08 Depok, West Java. The research method used in this study is descriptive with a quantitative approach. Data analysis used includes: Descriptive Statistical Test, Normality, Multicollinearity, Heteroscedasticity, Autocorrelation, Simple Linear Regression, Multiple Linear Regression, t Test (Partial), F Test (Simultaneous), Correlation Coefficient (R) and Determination Coefficient (R2). The results of the study indicate partially that motivation has a significant effect on employee performance as seen from the t test, the t count value is obtained > t table (9.916 > 1.673) and is significant 0.000 <0.05. Then for the work discipline variable, it has a significant effect on employee performance as seen from the t test, the t count value is obtained > t table (11.901 > 1.673) and is significant 0.000 <0.05. Meanwhile, from the results of the F test (simultaneous), a significance value of 0.000 (0.000 <0.05) and an F count value of 107.562 was obtained, which means that F count is greater than F table (107.562> 3.17) which means that the Motivation and Work Discipline variables have an effect on Employee Performance. From the results of the correlation coefficient test, an R value of 0.799 was obtained, which means that the Motivation and Work Discipline variables have a strong correlation level with Employee Performance. However, from the results of the determination coefficient test (R2), the adjusted R square value of 0.792 was obtained, which means that the influence of the Motivation and Work Discipline variables on Employee Performance in this study was 79.2% while the remaining 20.8% was influenced by other variables not examined in this study.